1974
DOI: 10.1042/bj1420465
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxytetracycline on insulin resistance in obese mice

Abstract: 1. Chronic oxytetracycline treatment was found to improve the insulin resistance of the obese-hyperglycaemic mouse. 2. The improved response to insulin was accompanied by decreased concentrations of circulating insulin and glucose, by a decrease in the lipid content of the liver and by an increase in the insulin-receptor sites of the liver and adipose tissue. 3. The increase in insulin-receptor sites preceded the fall in blood glucose. 4. Comparable studies done on food-restricted animals indicated that althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…7) insulin binding by hepatic plasma membranes from the ob/ob mouse (4,39), the db/db mouse (4), and the gold thioglucose rat (4), by adipocytes from the ob/ob mouse (39) and by monocytes from obese human subjects (11). The enhancement of insulin binding by caloric restriction in the ob/ob mouse can be prevented by administering exogenous insulin during this period (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) insulin binding by hepatic plasma membranes from the ob/ob mouse (4,39), the db/db mouse (4), and the gold thioglucose rat (4), by adipocytes from the ob/ob mouse (39) and by monocytes from obese human subjects (11). The enhancement of insulin binding by caloric restriction in the ob/ob mouse can be prevented by administering exogenous insulin during this period (4).…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of insulin binding by caloric restriction in the ob/ob mouse can be prevented by administering exogenous insulin during this period (4). Treatment of the ob/ob mouse with oxytetracycline also decreases insulin levels and increases insulin binding by both hepatic plasma membranes and adipocytes (39). New Zealand obese mice have increased insulin concentrations and decreased binding by hepatic plasma membranes (33).…”
Section: Discussionmentioning
confidence: 99%
“…Since oxytetracycline has been shown to increase the in vitro insulin sensitivity of ob/ob mouse muscle, to "normalize" in vivo glucose and insulin tolerance in ob/ob mice [5,6], and to potentiate the effects of exogenous insulin in depancreatectomized dogs [7,8], the drug appears to act by increasing target cell sensitivity to the catalytic actions of insulin.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier reports have demonstrated that the longterm administration of oxytetracycline to animals having either experimental diabetes or genetic diabetes-obesity results in a reduced severity of the diabetic symptoms [5][6][7][8]. Since oxytetracycline has been shown to increase the in vitro insulin sensitivity of ob/ob mouse muscle, to "normalize" in vivo glucose and insulin tolerance in ob/ob mice [5,6], and to potentiate the effects of exogenous insulin in depancreatectomized dogs [7,8], the drug appears to act by increasing target cell sensitivity to the catalytic actions of insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation